Letter from Charles T. Manatt - Charles T. Manatt:::::: (1974)
In this January 2, 1974 letter to Southern DSCC members, Charles T. Manatt reflects on 1973 as a year of progress in fundraising, voter registration, party organization, and candidate development. Looking ahead to 1974, he warns against complacency despite Watergate, emphasizes the challenges posed by reapportionment, and stresses the need for strong organization and voter registration efforts. He underscores the importance of party unity after the June primaries and encourages Democrats to work together toward success in the November elections.